Democracy, Liberty and Montesquieu: Constructing Accountable Order in African Conflict States. (8th January 2013) - Leonard, David K.
Abstract Without appropriate institutional checks multiparty democracy can rekindle violent conflicts rather than help to resolve them. The absolutism of 'imperial presidents' is at the root of many of Africa's civil wars and the restoration of this institution in post‐conflict states will not help them find security for their citizens. Following Montesquieu, I argue that 'liberty', in the form of checks on executive power, must accompany or precede multiparty democracy in post‐conflict reconstruction.